Konkurencja cenowa i pozacenowa na rynku nawozów mineralnych w Polsce - Piwowar, Arkadiusz (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
The phenomenon of the competition takes place on the market of mineral fertilizers and plays an important role in the processes of exchange. In order to create competitive advantages on the market of mineral fertilizers, the production and trade enterprises are using a variety of competition instruments, which outline the dimension of competition on the market. In this study are presented the theoretical considerations and empirical researches on the phenomenon of competition between two groups of market players on the market of mineral fertilizers in Poland: fertilizer producers and brokers